2018
DOI: 10.4049/jimmunol.1701287
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Macrophage Expansion in Pulmonary Hypertension Depends upon Mobilization of Blood-Borne Monocytes

Abstract: Pulmonary inflammation, which is characterized by the presence of perivascular macrophages, has been proposed as a key pathogenic driver of pulmonary hypertension (PH), a vascular disease with increasing global significance. However, the mechanisms of expansion of lung macrophages and the role of blood-borne monocytes in PH are poorly understood. Using multicolor flow cytometric analysis of blood in mouse and rat models of PH and patients with PH, an increase in blood monocytes was observed. In parallel, lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 80 publications
7
117
0
Order By: Relevance
“…3E) and reduce numbers of macrophages in lungs from MCT-injected and SuHx rats. Remarkably, macrophages have been implicated in the pathogenesis of PAH [34][35][36][37] . This mode of action that allow the blockade of CXCL12 without any effect on the two receptors favors cell homeostasis and the fact that these molecules influence several mechanisms involved in PAH pathobiology are particularly promising in this context.…”
Section: Discussionmentioning
confidence: 99%
“…3E) and reduce numbers of macrophages in lungs from MCT-injected and SuHx rats. Remarkably, macrophages have been implicated in the pathogenesis of PAH [34][35][36][37] . This mode of action that allow the blockade of CXCL12 without any effect on the two receptors favors cell homeostasis and the fact that these molecules influence several mechanisms involved in PAH pathobiology are particularly promising in this context.…”
Section: Discussionmentioning
confidence: 99%
“…In PH, patients' expression of chemokines, such CCL1, CCL2, CCL5 and CX3CL1, was increased in circulatory monocytes, along with increased pulmonary levels of CCl1, CCL2, CCL3, CLL3 and CX3CL1 [31]. In CX3CR1 (receptor for CX3CL1)-deficient mice, both pulmonary inflammation and vascular remodeling were reduced after exposure to hypoxia when compared to control mice [31]. Interestingly, in pulmonary vascular endothelial cells from PAH patients, excessive expression of CCL2 was observed, which acts as a chemoattractant for circulating inflammatory cells and as a growth factor for pulmonary arterial smooth muscle cells (PASMCs).…”
Section: Macrophagesmentioning
confidence: 98%
“…They might be involved in PH development through their production of cytokines [28][29][30]. Furthermore, the macrophages present in lung perivascular spaces in PAH are derived from peripheral blood monocytes [31], likely indicating their recruitment and differentiation due to pulmonary inflammation. However, chemokines, such as chemokine (C-C motif) ligand 2 (CCL2) and chemokine (C-X3-C motif) ligand 1 (CX3CL1) monocytes are recruited to the site of the inflammation and differentiate into inflammatory macrophages.…”
Section: Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological or genetic ablation of such chemokines and their receptors have been relevant to the pathogenesis of PH [ 3 , 37 ]. Recently, Florentin and colleagues investigated the role and mobilization of blood-borne circulating monocytes and their contribution to arteriolar wall remodeling [ 38 ]. They showed that genetic or pharmacological deficiency of C-X3-C motif chemokine receptor 1 (Cx3cr1)-expressing monocytes limited the recruitment of monocytes and the development of lung remodeling in hypoxia- and monocrotaline (MCT)-induced PH without amelioration of vascular hemodynamics [ 38 ].…”
Section: Macrophage-mediated Immunity In Pahmentioning
confidence: 99%